Panentheisms East and West - Clayton, Philip (Sophia, 2010)
In the West panentheism is known as the view that the world is contained within the divine, though God is also more than the world. I trace the history of this school of philosophy in both Eastern and Western traditions. Although the term is not widely known, the position in fact draws together a broad range of important positions in 20th and 21st century metaphysics, theology, and philosophy of religion. I conclude with some reflections on the practical importance of this position.